2013
DOI: 10.1016/j.ygeno.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dysfunctions in acute rejection after renal transplantation revealed by integrated analysis of transcription factor, microRNA and long noncoding RNA

Abstract: Acute rejection remains a problem in renal transplantation. To further illustrate the mechanism of rejection, we integrated protein array-based proteomics and RNA microarray-based genomics to investigate the transcription factor, microRNA and long noncoding RNA of biopsies of three patients with acute rejections and a control group. 99 transcription factors were identified in acute rejection biopsies compared to normal renal tissue. We correlated transcription factor data with microRNA and long noncoding RNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Mounting evidence indicated lncRNAs in blood could serve as novel biomarkers for the early diagnosis and prognosis prediction of human diseases [32-34]. In renal transplantation, the global lncRNA expression levels have been profiled in three AR renal biopsy tissues and control tissues from three renal tumor patients, and a total of 5339 lncRNAs were proven to differentially express between groups, among which five lncRNAs (AF113674, uc003wbj, uc010ftb, uc001fty, and AK129917) were selected for further validation and confirmed by quantificational real-time polymerase chain reaction (qRT-PCR) [16, 17]. In a recent clinical study, Lorenzen et al comprehensively analyzed the genome-wide lncRNA expression profiles in the urine samples (9 ATMR vs. 9 STA recipients), and found a summary of 4189 differentially expressed lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence indicated lncRNAs in blood could serve as novel biomarkers for the early diagnosis and prognosis prediction of human diseases [32-34]. In renal transplantation, the global lncRNA expression levels have been profiled in three AR renal biopsy tissues and control tissues from three renal tumor patients, and a total of 5339 lncRNAs were proven to differentially express between groups, among which five lncRNAs (AF113674, uc003wbj, uc010ftb, uc001fty, and AK129917) were selected for further validation and confirmed by quantificational real-time polymerase chain reaction (qRT-PCR) [16, 17]. In a recent clinical study, Lorenzen et al comprehensively analyzed the genome-wide lncRNA expression profiles in the urine samples (9 ATMR vs. 9 STA recipients), and found a summary of 4189 differentially expressed lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that lncRNAs could regulate gene expression at the transcriptional and/or post-transcriptional levels, and play fundamental roles in a diverse array of biological processes such as cell cycle control, development, carcinogenesis, and immune response [12-15]. A large number of dysregulated lncRNAs have been identified in the renal cortex tissues of AR recipients [16-18]. Recently, Lorenzen and colleagues have analyzed the lncRNA expression profiles in the urine of renal transplant recipients, and demonstrated that urinary RP11-354P17.15-001 could serve as a novel biomarker of acute T cell-mediated rejection (ATMR) of renal allografts [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lncRNA DQ786227 was suggested to mediate cell malignant transformation induced by benzopyrene [11]. Simultaneously, aberrant transcript profiles of lncRNAs were observed in non-neoplastic diseases, such as ventricular septal defect and acute renal rejection [12,13]. Recently, the majority of studies have focused on the mechanisms of lncRNA regulation of their target coding genes.…”
Section: Introductionmentioning
confidence: 99%
“…(25,26). To decrease the number of false-positive results, we integrated the predicted targets from miRanda, TargetScan and PicTar based on sequence complementarity, evolutionary conservation and free energy of RNA duplexes, which predicted by at least two of three databases were accepted as positive (25). (TFs were treated as genes when predicting miRNA→TF regulatory relations).…”
Section: Patient Samples and Ethics Statementmentioning
confidence: 99%